2014
DOI: 10.3390/ijerph111010062
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cities in Reducing Smoking in China

Abstract: China is the epicenter of the global tobacco epidemic. China grows more tobacco, produces more cigarettes, makes more profits from tobacco and has more smokers than any other nation in the world. Approximately one million smokers in China die annually from diseases caused by smoking, and this estimate is expected to reach over two million by 2020. China cities have a unique opportunity and role to play in leading the tobacco control charge from the “bottom up”. The Emory Global Health Institute—China Tobacco C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In China, cities may play an important role in changing the social norms of tobacco use from a bottom-up approach through efforts such as public education and media campaigns. By educating citizens, as well as taking the charge on implementing and enforcing smoke-free policies at the local level, cities have the opportunity and responsibility to increase acceptance and support for smoke-free laws, thus enhancing the likelihood of their success 37…”
Section: Discussionmentioning
confidence: 99%
“…In China, cities may play an important role in changing the social norms of tobacco use from a bottom-up approach through efforts such as public education and media campaigns. By educating citizens, as well as taking the charge on implementing and enforcing smoke-free policies at the local level, cities have the opportunity and responsibility to increase acceptance and support for smoke-free laws, thus enhancing the likelihood of their success 37…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that cities play a critical role in changing social norms of tobacco use and may be the driving force for this change in developing countries. 38 Hence, tobacco bans in cities hosting mega-events are important strategies to initiate and sustain tobacco-free social norm changes. However, it is important to recognize that there are limitations to this approach.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the partnership, which was established in 2008, is to reduce the health, social, environmental and economic burdens of tobacco through several initiatives implemented in 17 Chinese cities 25. The 17 grantee cities were allowed to decide where to focus their efforts based on each city's unique context.…”
Section: Methodsmentioning
confidence: 99%